Fatty Acid Profile of Quassia undulata Oil Traditionally Extracted in Senegal - Ndiaye, Seyni; Diop, El Hadj Moussa; Ndiaye, Edouard Mbarick; Ndiaye, Bou; Ayessou, Nicolas C. M.; Cisse, Mady (Discoveries in Agriculture and Food Sciences, 2025)
This study examines the influence of Piliostigma thonningii leaves on the composition and physicochemical properties of Quassia undulata oil traditionally extracted by Bassari women in southeastern Senegal. Oils were produced with and without the presence of P. thonningii leaves following local extraction methods. Infrared spectroscopy (FT-IR) and gas chromatography (GC-FID) were used to determine their chemical composition and fatty acid profiles. The results show that both oils are predominantly composed of oleic acid (≈61–62%) and stearic acid (≈19%), with minor amounts of palmitic, linoleic, and linolenic acids. The total content of polyunsaturated fatty acids remains low (≈6%), indicating high oxidative stability. The oil extracted without P. thonningii leaves contained more double bonds, reflecting a higher degree of unsaturation. No statistically significant differences were found between the two samples, although a slight reduction in polyunsaturated fatty acids was observed in the oil obtained with P. thonningii, likely due to heat exposure during the purification step. Overall, Q. undulata oil is characterized by a high monounsaturated fatty acid content, good oxidative stability, and a solid texture at ambient temperature, making it a potential candidate for food, cosmetic, and pharmaceutical applications.